Obstacles to International Policy Coordination, and How to Overcome Them - Ostry, Jonathan (Staff Discussion Notes; Staff Discussion Notes ;, 2013)
In bilateral and multilateral surveillance, countries are often urged to consider alternative policies that would result in superior outcomes for the country itself and, perhaps serendipitously, for the world economy. While it is possible that policy makers in the country do not fully recognize the benefits of proposed alternative policies, it is also possible that the existing policies are the best that they can deliver, given their various constraints, including political. In order for the policy makers to be able and willing to implement the better policies some quid pro quo may be required-such as a favorable policy adjustment in the recipients of the spillovers; identifying such mutually beneficial trades is the essence of international policy coordination. We see four general guideposts in terms of the search for globally desirable solutions. First, all parties need to identify the nature of spillovers from their policies and be open to making adjustments to enhance net positive spillovers in exchange for commensurate benefits from others; but second, with countries transparent about the spillovers as they see them, an honest broker is likely to be needed to scrutinize the different positions, given the inherent biases at the country level. Third, given the need for policy agendas to be multilaterally consistent, special scrutiny is needed when policies exacerbate global imbalances and currency misalignments; and fourth, by the same token, special scrutiny is also needed when one country's policies has a perceptible adverse impact on financial-stability risks elsewhere.